IEEE Symposium on Ultrasonics, 2003
DOI: 10.1109/ultsym.2003.1293316
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered AlN thin films on Si and electrodes for MEMS resonators: relationship between surface quality microstructure and film properties

Abstract: Aluminum nitride thin films grown by reactive AC magnetron sputtering are characterized using several metrology techniques to examine the correlation between surface quality, microstructure and piezoelectric properties. Atomic force microscopy, X-ray diffraction and electron microscopy, and are employed to characterize the microstructure. . A range of substrate coatings is explored to understand the impact of topography on film crystallinity and piezoelectric performance. A first order approximation model prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 4 publications
1
24
0
1
Order By: Relevance
“…First, it is important to note that a widening of the RC alone does not produce a significant deterioration of the piezoelectric activity, unless other defects are also present in the samples. This result can be predicted by simple geometrical considerations [23]. On the other hand, the presence of inclined grains with orientations others than (00-2) is clearly linked to the reduction of the piezoelectric activity.…”
Section: Structural and Piezoelectric Characterization Of Aln Filmsmentioning
confidence: 67%
“…First, it is important to note that a widening of the RC alone does not produce a significant deterioration of the piezoelectric activity, unless other defects are also present in the samples. This result can be predicted by simple geometrical considerations [23]. On the other hand, the presence of inclined grains with orientations others than (00-2) is clearly linked to the reduction of the piezoelectric activity.…”
Section: Structural and Piezoelectric Characterization Of Aln Filmsmentioning
confidence: 67%
“…It can be noticed that AIN films grown on polished substrates exhibit excellent piezoelectric activity, almost independent of the RC of the underlying Ir electrode (ranging from 2° to 5°) and the RC around the (00-2)-AIN reflection (ranging from 1.5° to 3°). The widening of the RCs of both Ir and AIN is very likely related with a "geometrical" effect (growth on tilted surfaces) rather than to a real worsening of the crystalline structure [27], Hence, it was found that it is possible to produce highly oriented AIN films even on Ir electrodes of different quality. The best achievements were AIN films 200 nm-thick with a RC 1.57°-wide grown on Ir substrates with a RC of 3.8°.…”
Section: Setting Of the Deposition Parametersmentioning
confidence: 98%
“…It is evident that the layer on which AlN is deposited has a strong influence on the AlN quality [4]. High c-axis orientation of AlN on smooth crystalline surfaces such as Sapphire [5] and Silicon [4] has been reported.…”
Section: Solidly Mounted Baw Resonatorsmentioning
confidence: 99%